2021
DOI: 10.1038/s41366-021-00801-w
|View full text |Cite
|
Sign up to set email alerts
|

ω-3PUFA supplementation ameliorates adipose tissue inflammation and insulin-stimulated glucose disposal in subjects with obesity: a potential role for apolipoprotein E

Abstract: Background Long chain omega-3 polyunsaturated fatty acids (ω-3PUFA) supplementation in animal models of diet-induced obesity has consistently shown to improve insulin sensitivity. The same is not always reported in human studies with insulin resistant (IR) subjects with obesity. Objective We studied whether high-dose ω-3PUFA supplementation for 3 months improves insulin sensitivity and adipose tissue (AT) inflammation in IR subjects with obesity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…We strongly support the need for further studies which will help elucidate (1) the source of increased APOE we observed in our subjects, (2) the mechanism(s) responsible for the observed improvement in glucose disposal, and (3) the functional status of adipose tissue resident macrophage post-fish oil supplementation. APOE has been reported to have anti inflammatory properties [3][4][5][6].…”
supporting
confidence: 72%
See 1 more Smart Citation
“…We strongly support the need for further studies which will help elucidate (1) the source of increased APOE we observed in our subjects, (2) the mechanism(s) responsible for the observed improvement in glucose disposal, and (3) the functional status of adipose tissue resident macrophage post-fish oil supplementation. APOE has been reported to have anti inflammatory properties [3][4][5][6].…”
supporting
confidence: 72%
“…
We would like to thank the Editor for giving us the opportunity to respond to the comments made by Dr. Poledne R. et al regarding our recent publication, "ω-3PUFA supplementation ameliorates adipose tissue inflammation and insulin-stimulated glucose disposal in subjects with obesity: a potential role for apolipoprotein E" [1]. We also thank Dr. Poledne R. et al for reading our work and appreciate their comment.The authors have offered an alternative explanation for our findings.
…”
mentioning
confidence: 91%
“…The present study included participants with a normal body weight – which was preserved throughout the intervention. In obese subjects, similar results in lipid profile might be observed [ 46 ], also accompanied by a reduction in inflammatory markers [ 47 ].…”
Section: Discussionsupporting
confidence: 57%
“…Obesityinduced chronic inflammation is not confined to adipose and liver since there are reports of proinflammatory pathway activation in the CNS, the gastrointestinal tract, muscle, and pancreatic islets, consistent with an intra-and interorgan network of crosstalk in these complex heterogeneous disorders (Lee and Olefsky, 2021). A sizable literature exists exploring various cytokines, adipokines, lipid species, and other factors released from adipose tissue that may contribute to systemic metabolic dysfunction (Lago et al, 2007;Hernandez et al, 2021;Vegiopoulos et al, 2017).…”
Section: Adipose Tissue Exosome Biologymentioning
confidence: 99%